2013
DOI: 10.1262/jrd.2012-119
|View full text |Cite
|
Sign up to set email alerts
|

Superstimulation of Follicular Growth in Thai Native Heifers by a Single Administration of Follicle Stimulating Hormone Dissolved in Polyvinylpyrrolidone

Abstract: This study was undertaken to determine whether a single i.m. injection of FSH dissolved in 10 ml of 30% (wt/vol) polyvinylpyrrolidone (PVP; MW=40,000) to form FSHp would induce follicular growth in Thai native heifers and to determine its optimal dose. In Group 1, heifers (n=4) were given multiple i.m. injections of FSHp every 12 h for 3 days at decreasing doses, for a total of 100 mg (control). In Groups 2, 3 and 4, heifers (n=4 in each group) were given single i.m. injections of FSHp at 50, 100 and 150 mg. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…On the basis of the rapid clearance of FSH (w5 hours) [39], regardless of the dose administered [55], an alternative could be to modify hormone absorption. Modifications examined have included changing the route administration (subcutaneous injection, [55][56][57]) or mixing the pFSH with polymers, such as polyvinylpyrrolidone [58], aluminum hydroxide gel [59] or HA [42] to reduce the rate of absorption. Tríbulo et al [42] reported satisfactory superovulatory results after treating Table 1 Summary of cumulus-oocyte complex yield and in vitro embryo production (mean AE standard error or percentage) in nonlactating Holstein cows that were not treated (control), treated with 200 mg of porcine FSH (pFSH; F200) in twice-daily injections or 200 or 300 mg of pFSH as a single injection in 0.5% hyaluronan (F200HA and F300HA).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the rapid clearance of FSH (w5 hours) [39], regardless of the dose administered [55], an alternative could be to modify hormone absorption. Modifications examined have included changing the route administration (subcutaneous injection, [55][56][57]) or mixing the pFSH with polymers, such as polyvinylpyrrolidone [58], aluminum hydroxide gel [59] or HA [42] to reduce the rate of absorption. Tríbulo et al [42] reported satisfactory superovulatory results after treating Table 1 Summary of cumulus-oocyte complex yield and in vitro embryo production (mean AE standard error or percentage) in nonlactating Holstein cows that were not treated (control), treated with 200 mg of porcine FSH (pFSH; F200) in twice-daily injections or 200 or 300 mg of pFSH as a single injection in 0.5% hyaluronan (F200HA and F300HA).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single superovulation injection with FSH in degradable polymers to sustain hormone release has been studied in ruminants (Lopez-Sebastian et al 1993;Yamamoto et al 1994;Satoh et al 1996;Sugano and Shinogi 1999;D'Alessandro et al 2001;Kimura et al 2007;Tribulo et al 2012). In cattle, administration of FSH dissolved in various substances, including polyvinylpyrrolidone, aluminum hydroxide gel https://doi.org/10.17221/52/2016-VETMED or hyaluronan (HA), increased ovarian responses compared to multiple FSH injections (Bo et al 1994;Yamamoto et al 1995;Kimura et al 2007;Tribulo et al 2012;Chasombat et al 2013). HA is a biological polymer that is abundantly expressed in many tissues.…”
mentioning
confidence: 99%
“…The FSH suspension in PVP characterized with high viscosity, which created some difficulties to achieve a homogeneous mixture and limited its practical application (6,23). However, as no other undesirable effects have been demonstrated, PVP is still used in some countries as an adjuvant in commercial FSH preparations (10).…”
Section: Conventional Methods Of Inducing Superovulation In Cattlementioning
confidence: 99%